Aproximación al análisis de la estructura económica de las poblaciones agrarias aragonesas - Chueca Diago, María Carmen; Frutos Mejías, Luisa María; Solans Castro, Manuela (Geographicalia, 2017)
The typification of agricultural holdings according not only to their area but also to their economical significance provides an useful information. It helps to reveal the problems and viability of agricultural holdings and therefore to design a suitable politics of structures. The Spanish Agricultural Statistics of 1982 and 1989 include data at the level of autonomic communities. These allow a first structural classification despite their shortcomings. The elaboration of that information for Aragon leads to the conclusion that there is a defective agricultural structure with an excessive number of farms of a small economical significance according to their gross margin. To a great extent that is due to the prominence of cereals as a main and secondary crop and also to a scarce especialization. Nevertheless some significant differences can be found among the various farm type of holding, of which the growing of fruits and vegetables is the most profitable.